Clinical spectrum and long-term follow-up of 14 cases with G6PC3 mutations from the French severe congenital neutropenia registry - Desplantes, Claire (Orphanet J Rare Dis, 2014)
BACKGROUND: The purpose of this study was to describe the natural history of severe congenital neutropenia (SCN) in 14 patients with G6PC3 mutations and enrolled in the French SCN registry. METHODS: Among 605 patients included in the French SCN registry, we identified 8 pedigrees that included 14 patients with autosomal recessive G6PC3 mutations. RESULTS: Median age at the last visit was 22.4 years. All patients had developed various comordibities, including prominent veins (n = 12), cardiac malformations (n = 12), intellectual disability (n = 7), and myopathic syndrome with recurrent painful cramps (n = 1). Three patients developed Crohn’s disease, and five had chronic diarrhea with steatorrhea. Neutropenia was profound (<0.5 × 10(9)/l) in almost all cases at diagnosis and could marginally fluctuate. The bone marrow smears exhibited mild late-stage granulopoeitic defects. One patient developed myelodysplasia followed by acute myelogenous leukemia with translocation (18, 21) at age 14 years, cured by chemotherapy and hematopoietic stem cell transplantation. Four deaths occurred, including one from sepsis at age 5, one from pulmonary late-stage insufficiency at age 19, and two from sudden death, both at age 30 years. A new homozygous mutation (c.249G > A /p.Trp83*) was detected in one pedigree. CONCLUSIONS: Severe congenital neutropenia with autosomal recessive G6PC3 mutations is associated with considerable clinical heterogeneity. This series includes the first described case of malignancy in this neutropenia.